2019
DOI: 10.1101/784868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SPF45/RBM17-dependent, but not U2AF-dependent, splicing in a distinct subset of human short introns

Abstract: Human pre-mRNA introns vary in size from under fifty to over a million nucleotides. We searched for specific splicing factors involved in human short introns by screening siRNAs against 154 human nuclear proteins for activity on a model short 56-nucleotide intron-containing HNRNPH1 pre-mRNA. We identified a known alternative splicing regulator SPF45 (RBM17) as a general splicing factor that is essential to splice out this 56-nt intron. Whole-transcriptome sequencing of SPF45 deficient cells revealed that SPF45… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…SF3B1 ULM5mut, in which all ULMs except ULM5 were preserved, restored splicing to similar levels as WT SF3B1. This result is consistent with the ability of SF3B1 ULM5mut to bind and co-immunoprecipitate with U2AF2, yet leaves open the possibility of some ULM -UHM redundancy (e.g., a potential ability of PUF60 or SPF45 to substitute for U2AF2 (34,38)). Altogether, these results demonstrate the importance of the U2AF2 UHM and SF3B1 ULMs for pre-mRNA splicing functions in cells.…”
Section: The U2af2 Uhm -Sf3b1 Ulm Interface Contributes To Splicing O...supporting
confidence: 79%
See 2 more Smart Citations
“…SF3B1 ULM5mut, in which all ULMs except ULM5 were preserved, restored splicing to similar levels as WT SF3B1. This result is consistent with the ability of SF3B1 ULM5mut to bind and co-immunoprecipitate with U2AF2, yet leaves open the possibility of some ULM -UHM redundancy (e.g., a potential ability of PUF60 or SPF45 to substitute for U2AF2 (34,38)). Altogether, these results demonstrate the importance of the U2AF2 UHM and SF3B1 ULMs for pre-mRNA splicing functions in cells.…”
Section: The U2af2 Uhm -Sf3b1 Ulm Interface Contributes To Splicing O...supporting
confidence: 79%
“…In principle, the consequences of disrupting the U2AF2 UHM and SF3B1 ULMs in these systems could result from interactions with other partners, e.g., SF1 for U2AF2 or other UHM-containing splicing factors such as SPF45 or Tat-SF1 for SF3B1 (22,34). However, we note that roles for SF1, SPF45 or Tat-SF1 in pre-mRNA splicing are conditional and rare (8,34,40,51). Indeed, reduced SF1 levels had little effect on splicing of the U2AF2-responsive splice sites examined here (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Keiper et al reported that splicing factors Smu1 and RED facilitate the activation of spliceosomal B complexes assembled on short introns (Keiper et al, 2019). Interestingly, recent results by the Mayeda lab also revealed a role for SPF45 in splicing of short introns (Fukumura et al, 2019). It seems likely that architectural built-in features of the spliceosome, including the need for multiple UHM-ULM interactions of SPF45 with SF1/BBP, U2AF65 and SF3B1 for SPF45-mediated control (Corsini et al, 2007) are behind the regulatory properties of SPF45/SR140/CHERP and the substrate length features (activation of short introns, repression of short exons) of its targets.…”
Section: Mechanism Of Splicing Regulationmentioning
confidence: 99%
“…A previous study of splicing in mouse neurons showed that RBM17 normally represses the splicing of cryptic junctions and its loss leads to the inclusion of intronic elements in mature transcripts 46 . More recently, siRNA screening against 154 human nuclear proteins identified that RBM17 is essential in the efficient splicing of many short introns and such splicing regulation is determined by the length of the poly-pyrimidine tract (PPT) followed by the 3' splice site 47 . Exonization of intronic coding cassettes normally creates frameshifts or introduces PTCs 48,49 .…”
Section: Discussionmentioning
confidence: 99%